Potential of methacrylated acemannan for exerting antioxidant-, cell proliferation-, and cell migration-inducing activities in vitro - Meng-Han Chou; Yu-Hsu Chen; Ming-Te Cheng; Hung-Chi Chiang; Hou-Wen Chen; Ching-Wei Wang (BMC, 2023)
Abstract Background Acemannan is an acetylated polysaccharide of Aloe vera extract with antimicrobial, antitumor, antiviral, and antioxidant activities. This study aims to optimize the synthesis of acemannan from methacrylate powder using a simple method and characterize it for potential use as a wound-healing agent. Methods Acemannan was purified from methacrylated acemannan and characterized using high-performance liquid chromatography (HPLC), Fourier-transform infrared spectroscopy (FTIR), and 1H-nuclear magnetic resonance (NMR). 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assays were performed to investigate the antioxidant activity of acemannan and its effects on cell proliferation and oxidative stress damage, respectively. Further, a migration assay was conducted to determine the wound healing properties of acemannan. Results We successfully optimized the synthesis of acemannan from methacrylate powder using a simple method. Our results demonstrated that methacrylated acemannan was identified as a polysaccharide with an acetylation degree similar to that in A. vera, with the FTIR revealing peaks at 1739.94 cm−1 (C = O stretching vibration), 1370 cm−1 (deformation of the H-C-OH bonds), and 1370 cm−1 (C-O-C asymmetric stretching vibration); 1H NMR showed an acetylation degree of 1.202. The DPPH results showed the highest antioxidant activity of acemannan with a 45% radical clearance rate, compared to malvidin, CoQ10, and water. Moreover, 2000 µg/mL acemannan showed the most optimal concentration for inducing cell proliferation, while 5 µg/mL acemannan induced the highest cell migration after 3 h. In addition, MTT assay findings showed that after 24 h, acemannan treatment successfully recovered cell damage due to H2O2 pre-treatment. Conclusion Our study provides a suitable technique for effective acemannan production and presents acemannan as a potential agent for use in accelerating wound healing through its antioxidant properties, as well as cell proliferation- and migration-inducing activities.